Neoconservatives and Eternal Cold War - Mario Del Pero (Scienza & Politica, 2019)
The article discusses the genesis of U.S. neoconservatism – understood primarily as intellectual movement and political pressure group – and its foreign policy positions from the 1970s to today. It offers a definition of the movement centred on the liberal and universal nature of neoconservatism, and its ensuing rejection of the limitations to the sovereignty of the United States caused by the many interdependencies that have characterized the global order of the past fifty years.